Analytical Inquiry of Cfo Responsibilities: Aggregate Analysis Of Perceptual Differences Among Sda Conference Leaders In The Usa, Canada And Bermuda - Brown Sr., Theodore (Archives of Business Research, 2016)
The basis of this investigation was incited by the notion that the perceptions of Seventh-day Adventist (SDA) Conference leadership significantly impacts how the responsibilities of Chief Financial Officers (CFOs) are perceived in terms of their understanding and working knowledge of the importance and performance of CFO duties. Data was collected from a purposeful sample of N=399 at fifty-seven SDA Local Conferences in the United States of America (USA), Canada and Bermuda. A Mixed-Methods sequential exploratory research design utilizing Descriptive Statistics and Student-Newman-Keuls Post-Hoc Tests reflected significant differences among the aggregate results of conference leaders consisting of presidents CEOs, treasurers CFO, and board members BM, concerning CFO responsibilities. Discussion and Conclusions include potential conflicting leadership expectations of the CFO’s responsibilities, and a negative influence on the organizational culture and climate. Implications are applicable to organizations where leadership expectations of the CFO’s responsibilities have changed or may not be clearly defined or understood.